O potencial de um grupo colaborativo para a constituição do professor coordenador como formador de docentes - Rodrigues, Kátia Martins (2017)
This research investigates the potential of a Collaborative Group to the Teacher Coordinator (TC) constitution as a teacher educator. These professionals are responsible, among others school requests, of the in-service teachers continued education, in different times and formative spaces, such as: Collective Pedagogical Work Classes, pedagogical meetings, Class Council meetings and classroom observations. The starting point of this research was the problem regarding the continued education – during the work hours – of the Mathematics teachers, because this is considered by the TC, specialist or not, as the most complex and hardest area to be followed. As theoretical background, was adopted the constructs of Fullan and Hargreaves (2000), Pérez Gómez (2001), Imbernón (2010), Cochran-Smith and Lytle (1999), Crecci and Fiorentini (2015), Placco, Almeida and Souza (2011, 2012, 2015), André (2010), Passos (2016), Marcelo Garcia (1996, 1999), Altet (2000), among others. The research was developed following a qualitative methodological approach using different methodological procedures for the data collection: records of the formative meeting carried on the group; written records of the participants and the researcher and a profiling questionnaire. The research subjects are 14 Teacher Coordinators who work in the final years of Primary and High School located on the east zone of São Paulo. The results obtained indicated this group as a potential space to reveal the former’s feelings related to the in-service education of the Mathematics teachers; allowed the exposure of barriers and the announcement of possibilities in relation to the role as a former of the Teacher Coordinator; promoted critical thinking and collaboration using questioning and investigative posture, and encouraged the shared learning building up from the others view and contribution. In the formative process developed in this collaborative group, the teachers, Math specialists or not, presented the same difficulties with regard to the work as a Coordinator. Thus, it has become clear that the TC qualification should be focused on the role as a pedagogical former, independent of their teachers expertise area. This research brings contributions to the improvement of the professionals who work as educators; besides validate the importance of the collaborative work in the school and continued education using critical and reflexive views